2016
DOI: 10.1007/s00383-016-3858-5
|View full text |Cite
|
Sign up to set email alerts
|

Can neoadjuvant chemotherapy reduce the surgical risks for localized neuroblastoma patients with image-defined risk factors at the time of diagnosis?

Abstract: Only 27 % of the tumors with IDRFs became negative for IDRFs after chemotherapy. For negative IDRFs, tumors should shrink to <20 % of the volume at the time of diagnosis. Stage L2 tumors may have a potential risk for surgery even after neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…They also found that there were different rates of IDRF decrease among MYCN ‐amplified versus nonamplified tumors. Yoneda et al 29 investigated how IDRFs within a tumor can change over the course of neoadjuvant chemotherapy. Further studies are needed to better elucidate how changes in IDRF number over the entire treatment course may be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that there were different rates of IDRF decrease among MYCN ‐amplified versus nonamplified tumors. Yoneda et al 29 investigated how IDRFs within a tumor can change over the course of neoadjuvant chemotherapy. Further studies are needed to better elucidate how changes in IDRF number over the entire treatment course may be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that there were different rates of IDRF decrease among MYCN-amplified versus nonamplified tumors. Yoneda et al 29 are associated with decreased survival and histopathology such as MYCN amplification and high MKI.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a rate of decrease of 60%. Only 27% of patients with stage L2 tumors had no IDRFs after preoperative chemotherapy [7,17]. Thus, patients with stage L2 tumors may have a potential risk for surgery even after neoadjuvant chemotherapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, surgery was to be limited to biopsy with the expectation of a more safe and effective excision after neoadjuvant chemotherapy [ 4 6 ]. However, Yoneda et al reported that the surgical complication rate remained the same regardless of whether neoadjuvant chemotherapy reduced the number of IDRFs or not [ 7 ]. Simon et al found that the presence of IDRFs did not indicate unresectability and could not improve the predicted outcome of localized neuroblastoma [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…До сих пор нет единого мнения о числе курсов ПХТ, необходимых перед операцией. Некоторые исследования показали уменьшение факторов риска лишь на 15 % после ПХТ [37]. В то время как другие показали снижение коли-чества, выявленных ранее факторов риска, примерно у половины (54 %) включенных в исследование пациентов, при том, что это уменьшение было пропорционально степени регресса первичной опухоли и позитивно коррелировало с общим числом факторов риска при диагнозе [38].…”
Section: рис 4 послеоперационные осложнения у пациентов с факторамиunclassified